2017
DOI: 10.1111/edt.12349
|View full text |Cite
|
Sign up to set email alerts
|

Association of traumatic head injuries and maxillofacial fractures: A retrospective study

Abstract: There was a high prevalence of THI among patients with MFF (69.98%). RTA, nasal bone, zygomatic complex, zygomatic arch, orbital wall, maxillary sinus wall and mandibular alveolar process fractures were significantly associated with THI in patients who sustained a MFF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 26 publications
11
58
1
Order By: Relevance
“…Men were the victims most affected by automotive accidents, confirming previous findings [5,9,12,16,[20][21][22]. Although high, the sex ratio in this study was lower than that observed in India .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Men were the victims most affected by automotive accidents, confirming previous findings [5,9,12,16,[20][21][22]. Although high, the sex ratio in this study was lower than that observed in India .…”
Section: Discussionsupporting
confidence: 90%
“…This system is poorly equipped to deal with violations against traffic rules [18]. The lack of interest in wearing a motorcycle helmet or seat belt, bad road conditions, nonapplication of road traffic rules (negligence and recklessness while driving) or inadequate traffic law enforcement by police (especially in case of motorcyclists) may explain the reason for road traffic accident [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cranio‐maxillofacial trauma is the most prevalent among the countless types of trauma and is a growing cause of concern in the public health setting worldwide, due to it being responsible for high morbidity and mortality rates. At present, this type of trauma exceeds the incidence of caries and periodontal disease, with traumatic brain injury being the main cause of incapacity and death in children globally . Young patients with facial fractures represent a considerable proportion of cases requiring hospital admission, bringing colossal costs to public administration, in addition to representing an important factor in the overstretching of hospital services …”
Section: Introductionmentioning
confidence: 99%